NILAI PENDIDIKAN KARAKTER DALAM PEWARISAN TARI BARIS JOJOR LUTUNG JENUK DI DESA SELULUNG KINTAMANI - Dewa Gede Satya Adi Maha Utamia; I Kadek Indrawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Jojor Lutung Jenuk Baris Dance, which originates from Selulung Village, Kintamani, Bali, has become a symbol of cultural heritage that is rich in values ​​and character education. This research aims to think in depth about the values ​​of character education contained in the process of inheriting this dance in Selulung Village. Qualitative research methods with an ethnographic approach are the main basis for exploring detailed data through literature studies, in-depth interviews and documentation. The research results illustrate essential values ​​such as honesty, discipline, cooperation, loyalty, courage and creativity which are reflected in every aspect of this dance. The inheritance of these values ​​occurs through the ulu apad customary system, which builds awareness of responsibility and order in society regarding each person's role. This dance is not only a representation of art, but also a medium for in-depth character formation. The conclusion of this research shows that the Jojor Lutung Jenuk Baris Dance not only maintains the richness of cultural heritage, but also becomes a moral and ethical foundation for the people of Selulung Village. A deep understanding of these values ​​helps communities strengthen their identity in a context of harmony and tolerance, and plays a role in maintaining the continuity of a very valuable cultural heritage.